Polscy zesłańcy na Syberii Zachodniej w latach 60.–90. XIX wieku. Między mitem a rzeczywistością - Caban, Wiesław; Michalska-Bracha, Lidia (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2018)
The article concerns individual and collective experiences of Poles deported to Siberia in the second half of the 19th century. It is based on the 19th century memoirs and Polish and Russian accounts from the 19th and 20th century. An integral part of the article is the problem of the myth of Siberia, and its picture of martyrdom of which perpetuated by the 19th century literature, romantic poetry, and memoirs, including the works of Agaton Giller’s. A noticeable role in the making of the myth of Siberia played the works of Zygmunt Librowicz’s (Poles in Siberia, Cracow 1884) and Michal Janik’s (History of Poles in Siberia, Cracow 1928), among others. The article mentions numerous factors creating the myth of Siberia, including the system of repressions against the deportees, the myth of the sentenced to katorga terms, the myths concerning the attitude of Russian administration and civilians to the deportees, the cooperation between Polish and Russian exiled revolutionaries and marriages between the deportees and local Siberian women.